Exploring the impact of leadership styles, ethical behavior, and organizational identification on workers' well-being - Gianni Onesti (Administrative Sciences, 2023)
This paper aims to assess workers' well-being through a survey of Italian firms by exploring the factors of leadership styles, ethical behavior, and organizational identification. In recent years, also due to the COVID-19 pandemic and technological progress, workers' well-being has increasingly become a fundamental driver for company strategy and governance. Workers are increasingly interested in their well-being and work-life balance rather than just their level of remuneration or position at work. The company's ability to strategically retain capable collaborators is, therefore, fundamental, especially in light of the recent increase in resignations. Based on a sample of workers in Italian firms during the post-COVID-19 period (the year 2022), this paper evaluates whether leadership styles, ethical behavior, and organizational identification are related to workers' well-being beyond the workplace. The empirical model allows for a clear and effective evaluation of several characteristics, enabling a more comprehensive understanding of the data that support management's strategic decisions regarding worker well-being policies.
Keywords: 350; business ethics; healthy workplace; leadership; management; organizational identification; well-being